OPTIMASI PROSES MI JAGUNG VARIETAS LOKAL DENGAN TEKNOLOGI EKSTRUSI - Atiqatul Maula; Didah Nur Faridah; Tjahja Muhandri (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Maize noodles processing is different from that of conventional noodles made of wheat flour. In pro-ducing non wheat (gluten free) noodles, engineering is needed in the manufacturing process to obtain noodles with good quality and similar to the physical quality of wheat noodles. Processing of maize noodles requires particular treatment, such as heating, shearing, and maize noodles processing with sheeting techniques had previously been reported. Maize noodles processing using extrusion technology has also been done, but in previous studies, the maize used was of the hybrid varieties. This study aims to identify the pasting properties of maize flour and optimize the processing of dried maize noodles from local variety obtained from Madura Island named Elos. Extrusion technology was used to produce maize noodles with good physical characteristics. This study used a cooking-forming single screw extruder and formula consisting of 100% maize flour (db), 70% moisture content, and 2% NaCl. The experimental design was a complete randomized factorial design with two process variables, i.e. extruder temperature setting (75, 90, and 105°C) and extruder screw speed setting (100, 130, and 160 rpm). Response surface methodology (RSM) was used for process optimization to obtain the best process conditions based on several physical characteristics as the responses, i.e. cooking loss, elongation, hardness and degree of gelatinization. The optimum process conditions resulted from the Design Expert 7.0 program were extruder temperature of 95°C and screw speed of 100 rpm. The optimum condition produced maize noodles with cooking loss of 10.11%, elongation of 156.73%, hardness of 6252 gf and degree of gelatinization of 92.26%, with a desirability value of 0.954.